Mulitnational corporations and economic transformation in Nigeria: a case analysis of MTN Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The activities of multinational corporations in Nigeria have remained a source of controversy and debate over the years. The study examined the impact of Mobile Telecommunication Network (MTN) as a multinational company in the economic transformation in Nigeria. Hence, the specific objective isto ascertain the extent of economic transformation impacted by MTN as a multinational company in Nigeria. The study adopted a qualitative research method as a result descriptive research design is used to guide the study. The qualitative descriptive study is a comprehensive summarization of every concept of events experience by individuals or groups of individuals. It involves the utilization of enormous data collated by government ministries, civil society groups and scholarly publications. The study discovered that MTN Nigeria has contributed significantly towards the economic transformation in Nigeria.
Keywords: International firms; Economic development and Service provider